The impact of linguistic substitution in what Al-Zubaidi (T: 1205 AH) was unique in in the bride’s crown. - Al-Hamdani, Riyad Muhammad Odah Hamad (Al-Adab Journal, 2022)
Praise be to God who taught by the pen, taught man what he did not know, and blessings and peace be upon our master Muhammad, the master of Arabs and non-Arabs, and upon his family and companions and those who followed them and followed their path until the Day of Judgment. And yet:Linguistic substitution is one of the important phenomena that had a great impact on building the Arabic lexicon, and on the multiplicity of connotations of words in it. The researcher here is trying to reveal the effect of the phenomenon of linguistic substitution in a number of words that were devoid of Arabic dictionaries and only appeared in Al-Zubaidi (T.: 1205 AH) in his crown.This study resulted in a set of results. The most important of them are the following:Many of the words mentioned by Al-Zubaydi came as a result of their exposure to the phenomenon of phonemic evolution, which depends on the length of time and the succession of generations. It was affected by phonemic evolution due to the passage of time, and the phonetic relationship that governs the development of these sounds with each other.The change that affected words with the process of substitution, most of it evolved from difficulty to ease, such as changing a sound with an easier sound than it, and because of it new words appear that have an origin that evolved from it.